Paradoxes of (dis)empowerment in the postcolony: women, culture and social capital in Ghana. Issue 1 (2nd January 2016) - Bawa, Sylvia
Abstract: Women's empowerment discourses in Africa involve contradictory desires from women on one hand and society at large on the other. This article argues that the traditional validation mechanisms for women's identities are crucial avenues for analysing both the conceptions and experiences of empowerment. Drawing on primary ethnographic data, I analyse paradoxes in women's empowerment discourses in postcolonial Ghanaian societies, where neoliberal discourses thrive side-by-side with collectivist–socialist cultural ideals. Using an example of social capital, gained largely through mothering, I suggest that, because women's relationships with capital are structured by local socio-cultural and global economic structures and relations, the theorisation and application of the concept of empowerment need to recognise the complicated relationships (with capital) that women negotiate on a daily basis.